Short Communication: Trees species diversity and indicator species in Bedugul forest ecosystem, Bali, Indonesia - SUTOMO SUTOMO; I DEWA PUTU DARMA; ARIEF PRIYADI; RAJIF IRYADI (Biodiversitas Journal of Biological Diversity, 2018)
Sutomo, Darma IDP, Priyadi A, Iryadi R. 2018. Trees species diversity and indicator species in Bedugul forest ecosystem, Bali, Indonesia. Biodiversitas 19: 2213-2218. Bedugul area is an endorheic basin landscape with 3 lakes namely, Beratan, Buyan, Tamblingan, which is surrounded by Bukit Mangu, Tapak and Lesung. Topography of the area shows sloping to steep slopes with altitude on the lake surface ± 1,100 m asl and the highest peak of Bukit Mangu 2002 m asl. Ecological studies have not been optimal so identification of comprehensive ecological potential is carried out. Measurement of tree vegetation diversity was carried out by Centered Quarter Method and important value ratio analysis and location elevation class. The results of the inventory of tree species diversity in the Bedugul Bali forest area recorded 35 species and 13 indicator tree species. From the number of indicator tree species in the Mangu hill forest area there are 5 types of Ficus sp, Platea latifolia, Polyosma integrifolia, Lindera sp. and Syzygium sp., Bukit Tapak forest area consists of 4 species, Casuarina junghuhniana,  Acronychia trifoliate,  Astronia spectabilis and Homalanthus giganteus, the forest area of ??Bukit Lesung consists of 4 types of Lophopetalum javanicum, Syzygium racemosum, Dysoxylum nutans and Dendrocnide peltata.